Integrating STAD and Quizizz to Enhance Learning Outcomes and Creativity in Elementary Social Studies Education - Andi, Andri; Hendrizal, Hendrizal; Aisyah, Siti; Kurniawan, Romi (Publikasi Pendidikan, 2026)
This study aimed to investigate the influence of the Student Teams Achievement Divisions (STAD) cooperative learning model assisted by the Quizizz application on learning outcomes and student creativity in Social Studies for Grade V elementary students. Employing a quantitative quasi-experimental design with a nonequivalent control group, the research involved 36 students divided into an experimental group (STAD + Quizizz) and a control group (conventional instruction). Data were collected through pretests and posttests measuring cognitive learning outcomes and creativity, with creativity assessed via open-ended tasks using Munandar’s fluency, flexibility, originality, and elaboration indicators. Data analysis utilized Multivariate Analysis of Variance (MANOVA) followed by independent t-tests after verifying parametric assumptions. The results revealed that the STAD-Quizizz intervention significantly and simultaneously improved both learning outcomes and creativity (Pillai’s Trace = 0.675, p = 0.002). Follow-up tests confirmed significant positive effects on learning outcomes (p = 0.002, d = 1.47) and creativity (p = 0.002, d = 1.98), with large effect sizes indicating strong practical impact. Students in the experimental group achieved substantially higher posttest scores and demonstrated enhanced creative thinking compared to the control group. In conclusion, integrating STAD with Quizizz effectively fosters academic mastery and creative dispositions, supporting its adoption as an innovative, student-centered pedagogical strategy in elementary Social Studies.